A novel fluorescent adhesive-assisted biomimetic mineralization. Issue 40 (7th September 2018) - Wang, Zhe; Ouyang, Yan; Wu, Zhifang; Zhang, Leiqing; Shao, Changyu; Fan, Jiayan; Zhang, Ling; Shi, Ying; Zhou, Zihuai; Pan, Haihua; Tang, Ruikang; Fu, Baiping
Abstract : We propose a novel fluorescent adhesive-assisted biomimetic mineralization strategy, based on a mild self-etch adhesive containing 25 wt% polyacrylic acid-stabilized amorphous calcium phosphate nanoparticles and 1 wt% sodium fluorescein. Abstract : We propose a novel fluorescent adhesive-assisted biomimetic mineralization strategy, based on which 1 wt% of sodium fluorescein and 25 wt% of polyacrylic acid stabilized amorphous calcium phosphate (PAA-ACP) nanoparticles were incorporated into a mild self-etch adhesive (Clearfil S3 Bond) as a fluorescent mineralizing adhesive. The characterization of the PAA-ACP nanoparticles indicates that they were spherical particles clustered together, each particle with a diameter of approximately 20–50 nm, in a metastable phase with two characteristic absorption peaks (1050 cm −1 and 580 cm −1 ). Our results suggest that the fluorescent mineralizing adhesive was non-cytotoxic with minimal esthetic interference and its fluorescence intensity did not significantly decrease within 6 months. Our data reveal that the fluorescent mineralizing adhesive could induce the extra- and intra-fibrillar remineralization of the reconstituted type I collagen, the demineralized enamel and dentin substrate. Our data demonstrate that a novel fluorescent adhesive-assisted biomimetic mineralization strategy will pave the way to design and produce anti-carious materials for the prevention of dental caries.